Motivation for collaborative cartography: an experiment in the Brazilian Army - Guedes, Carlos Eduardo (2022)
The present work addresses the theme of collaborative mapping applied to the context of the Brazilian Army, taking advantage of the gamification technique in order to increase the military engagement in a collaborative mapping system. It was experimentally verified that the game design elements (points, badges and leaderboards), in the way they were applied, did not enhance the motivation of the military. However, the work corroborated the thesis that the Collective Intelligence of the Brazilian Army is capable of producing advantageous mapping for the cartography of itself interest.